Teaching Music in the Seminary - Yardley, Anne Bagnall (Teaching theology and religion, 2003)
Teaching music in certain seminary contexts poses particular challenges for teaching and learning. The theme of disjuncture between teacher and student in courses that aim to incorporate music in the seminary curriculum are more vital than ever before because of the extreme cultural diversity of our population and integral nature of music in the worship life of religious communities. This essay tackles the difficulties associated with teaching worship music in seminaries where there are a plurality of religious traditions represented and a host of expectations held by diverse student bodies about what connotes worship music. Topics addressed include issues concerning terminology, repertoire, pedagogical methods for teaching worship music, and current issues in church music.